Combined measures to control the COVID-19 pandemic in Wuhan, Hubei, China: A narrative review (2020)
Coronavirus disease 2019 (COVID-19) is an emerging disease caused by the coronavirus, SARSCoV-2, which leads to severe respiratory infections in humans. COVID-19 was first reported in December 2019 in Wuhan city, a populated area of the Hubei province in China. As of now, Wuhan and other cities nearby have become safe places for locals. The rapid control of the spread of COVID-19 infection was made possible due to several interventions and measures that were undertaken in Wuhan. This narrative review study was designed to evaluate the emerging literature on the combined measures taken to control the COVID-19 pandemic in Wuhan city. Science Direct, Springer, Web of Science, and the PubMed data repositories were searched for studies published between December 1, 2019, and June 07, 2020. The referred ”preferred reporting items for systematic reviews and meta-analyses” (PRISMA) protocol was used to conduct this narrative review. A total of 330 research studies were found as a result of the initial search based on exclusion and inclusion criteria, and 30 articles were chosen on final evaluation. It was discovered that the combined measures to control the spread of COVID-19 in Wuhan included cordon sanitaire, social distancing, universal symptom surveys, quarantine strategies, and transport restrictions. Based on the recommendations presented in this review study, existing policies with regard to combined measures and public health policies can be enforced by other countries to implement a rapid control procedure to control the spread of the COVID-19 pandemic.